Primary Hyperparathyroidism with a Predominant Lesion of the Gastrointestinal Tract - E. Yu. Kudashkina; E. G. Gavrilenko; A. A. Yakushev; G. G. Totolyan; N. N. Petrenko; L. Yu. Ilchenko; I. G. Fedorov; I. G. Nikitin (SINAPS LLC, 2021)
Primary hyperparathyroidism is a common pathology, but it is fact that doctors of various specialties run against difficulties in diagnosinging. The variety of clinical manifestations causes a long period of diagnosis and, late start of treatment. The main symptoms of this pathology are described taking into account the pathogenesis. The most common laboratory markers of hyperparathyroidism are incrising level of parathyroid hormone and hypercalcemia. Imaging examination methods are used to establish primary hyperparathyroidism. Targeted ultrasound examination of the parathyroid glands should be performed in all patients with suspected calcium metabolism disorders.This article presents a clinical case of primary hyperparathyroidism with predominant gastrointestinal symptoms. The patient was twice admitted to the hospital with various clinical manifestations of damage to the gastrointestinal tract. Erosive gastritis, terminal ileitis, chronic pancreatitis, and cholelithiasis were identified. A differential diagnosis was made with small intestine lymphoma and Crohn's disease. In addition, there were General cerebral symptoms in the form of lethargy, rapid exhaustion. Due to severe electrolyte disorders, the patient was observed in the intensive care unit. Due to the development of mechanical jaundice, endoscopic retrograde cholangiopancreatography with papillosphincterotomy was performed. Based on hypercalcemia, elevated parathyroid hormone levels, and visualization of parathyroid gland formation, the diagnosis of primary hyperparathyroidism was established based on ultrasound data. An adenomectomy of the left lower parathyroid gland was performed. in the surgical department. The patient was discharged with positive dynamics in the form of improvement in General health, cessation of pain, regress of vomiting, expansion of motor activity. Betimes diagnosis and treatment of primary hyperparathyroidism, on the example of the described case, leads to complete relief of symptoms and improvement of the quality of life of patients.